Urban Chinese Malaysian's stereotypical labels toward the Malays and Indians in Peninsular Malaysia - Lee, Yok Fee; Gill, Sarjit S. (Human Resource Management Academic Research Society, 2022)
This paper aims to identify the forms of stereotypical labels used by urban Chinese Malaysians towards the Malays and Indians in a few major cities in Peninsular Malaysia. The significant stereotypical labels are described and discussed to understand urban Chinese’s opinion on the labels. This study employed a sequential mixed-method research approach to collect both qualitative and quantitative data. First, focus group discussion was employed to derive the ethnic stereotypical labels and their meaning. Next, a survey was conducted on 333 respondents in a few major cities in Peninsular Malaysia to identify the significant labels. Results show that stereotypical labels used by the urban Chinese can be divided into different categories, i.e., physical appearance, social status and character, and religion. The construction of the stereotypical labels is related to the concepts of race of Chinese and their interaction with other ethnic groups in everyday life. Result also shows that only a few traditional labels are popularly used and agreed by the urban Chinese. The Chinese inherit their ancestors’ worldview and concept of race, which could be considered ethnocentric.